Avaliação dos efeitos de fármacos imunomoduladores na infecção de Hamsters, Mesocricetus auratus, POR Ancylostoma ceylanicum (Loss, 1911) - Silvia Regina Costa Dias (2011)
This study aimed to evaluate, the effects of immunomodulatory drugs upon the immune response and parasitological patterns of hamsters infected with Ancylostoma ceylanicum. Four classes of drugs (immunosuppressants, anti-lymphocyte, anti-inflammatory andantihistamines drugs) were used in this study. Among the imunossupressors cyclosporin A (CsA) and prednisolone were tested. The results showed that CsA treatment does not interfere with the experimental hookworms infection. On the other hand, the treatmentwith prednisolone has altered the regulation of the immune system, affecting, directly the intestinal integrity and oviposition of A. ceylanicum. Treatment with anti-CD3 had no influence in the A. ceylanicum infection in hamsters, however, when associated with prednisolone, it was observed that the specific antibody alleviated the context of inflammation. Prostaglandins did not work as a inflammatory mediators of importance in the hookworms infection, in this study. There were no differences in parasitological and immunological aspects between animals treated or not with aspirin, diclofenac or etoricoxib and infected with A. ceylanicum. Animals treated with anti-histamine (loratadine and ranitidine) presented severe clinical signs and were euthanized after 24 days of infection. Weobserved an increase in the number of eliminated eggs and the number of peripheral eosinophils and neutrophils in animals treated with a combination of both drugs. We show that immunosuppressive drugs do not necessarily suppress the Th1 or Th2 organisms effector response but they are responsible for regulating this process. Therefore, aexacerbated immunoregulated response of the body leads to an imbalance in the infection by A. ceylanicum in the intestine, leading to conditions that exacerbate the intestinal inflammation and consequently damaging the development of adult worms and eggs elimination. The increase in intestinal inflammation, due to excessive regulation of immune response associated with a reduction in the number of goblet cells is responsible for the increased loss of intestinal mucosa. We show an inverse behavior between the number of goblet cells and inflammatory bowel disease: as highest were the number of goblet cells, lesstissue inflammation was present in the intestine. Thus, goblet cells were associated with protection of the intestinal mucosa in infection by A. ceylanicum.